2021
DOI: 10.3390/brainsci11060805
|View full text |Cite
|
Sign up to set email alerts
|

Opioid Antagonist in the Treatment of Ischemic Stroke

Abstract: Stroke is a leading cause of death and disability, and novel treatments need to be found, particularly drugs with neuroprotective and restorative effects. Lately, there has been an increased interest in the relationship between opioids and ischemic stroke. To further appreciate this association between opioids and stroke, we conducted a systematic review to investigate anti-opioid medication’s effectiveness in treating ischemic stroke. We used PubMed advanced-strategy and Google Scholar searches and only inclu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…Eight studies of opioid antagonists in stroke were reviewed. A systematic review published in 2021 that included four studies on naloxone ( n = 96) and three studies on nalmefene ( n = 916) was selected ( 69 ). From this review, one small study ( n = 44) on naloxone showed benefit on Neurological Status Score at 2 weeks ( p < 0.01) and one study ( n = 236) on nalmefene showed improvement on Glasgow Coma Scale (GCS) at 10 days ( p < 0.05) and NIHSS at 20 days ( p < 0.05) compared to controls (LOE C-LD).…”
Section: Resultsmentioning
confidence: 99%
“…Eight studies of opioid antagonists in stroke were reviewed. A systematic review published in 2021 that included four studies on naloxone ( n = 96) and three studies on nalmefene ( n = 916) was selected ( 69 ). From this review, one small study ( n = 44) on naloxone showed benefit on Neurological Status Score at 2 weeks ( p < 0.01) and one study ( n = 236) on nalmefene showed improvement on Glasgow Coma Scale (GCS) at 10 days ( p < 0.05) and NIHSS at 20 days ( p < 0.05) compared to controls (LOE C-LD).…”
Section: Resultsmentioning
confidence: 99%
“…Hence, this patient confirmed the fact that "drug addicts commonly take more than one drug with or without alcohol". Cerebrovascular accident was not commonly associated with narcotic addiction [12,11]. cerebral hemorrhage with amphetamine [3].…”
Section: Discussionmentioning
confidence: 99%
“…cerebral hemorrhage with amphetamine [3]. and cerebral infarction with opioids [11,12]. This patient was 28 years old and he had left hemiparesis.…”
Section: Discussionmentioning
confidence: 99%
“…With a higher affinity than that of morphine, naloxone binds morphine receptors in the brain to inhibit the action of $-endorphin, the most active endogenous opioid. Then it inactivates $-endorphin, relieves transmission failure and reverses neurological dysfunction induced by the ischemic penumbra in brain tissue areas with edema 6 . Meanwhile, naloxone increases blood flow in ischemic areas, inhibits arachidonic acid metabolism, regulates the balance of prostacyclin and thromboxane, improves microcirculation, alleviates reperfusion injury and cerebral oedema and promotes the recovery of ischemic neuronal function 7 .…”
Section: Introductionmentioning
confidence: 99%